Study of Topological Properties of Interconnection Networks - Sharma, Pinki; Kumar Katare, Rakesh; Begum, Reshma (International Journal of Computer Sciences and Engineering, 2020)
In this paper we have taken various interconnection networks. In order to study properties of those networks we have derived their geometrical patterns from their respective incidence matrices. We have also applied some logical operations on incidence matrices to study various properties of interconnection networks.